Assessing the Old Export Channel with Panel Cointegration Test: The Westerlund Panel Cointegration Test - Kuikeu, Oscar (European Scientific Journal, ESJ, 2026)
Background: According to the Old Export channel, the external competitiveness accounts for the dynamics of a country’s export performance. Nevertheless, the New Export Channel is now presented as the main framework in explaining export performance, with the domestic demand as the main driving force of exports. This reverse explanations is generally attributed to some stylized facts concerning the international trade, as in Africa the high tendency of these countries to have exports concentrated in natural resources a products for which the externational competiteveness have limited ground since the price of these raw materials products result from the law of supply and demand in the international markets; in Europe the difference in manufacturing performance between the Germany in the one hand and the France, Italy and Spain in the other, this difference resulting from the demand policy applies by the former mainly austerity policy. Aims: In a recent study, the literature reaches the conclusion that when the evidence of cointegration is strong, there is no hope of observing the New Export channel. In fact, the Old Export channel is mainly a long-term relationship while the New Export channe lis an short run evidence. Then the aim of thsi pape ris to revisit the issue of cointegration in the Model governing the Exports dynamics. Method: Currently, to test evidence of cointegration in the Model underlying the Exports dynamics, the standard cointegration technique has been used in the literature. Nevertheless, these ones are considered are first generation test. Then, to overcome the evidence of cointegration in the Model underlying the Exports dynamics, we use a second-generation cointegration test that relies on the pooled estimation of the model rather than individual or country estimates, and finally, the computation of the asymptotic p-value as usual. Main findings: According to the obtained results, the Old Export channel is well assessed into the CEMAC area since the second generation of panel cointegration cannot accept the null of no cointegration at the standard level according to the computed statistics. Conclusion: Despite the findings that when the evidence of cointegration is strong, there is no or little hope to observe the New Export channel in the short run, with this study, we reach another outcome according to which even when the evidence of cointegration is limited, there is no doubt that there is a cointegrating relationship or the assessment of the Old Export channel.